2010
DOI: 10.1051/0004-6361/201014075
|View full text |Cite
|
Sign up to set email alerts
|

The follow-up European VLBI Network observations of twelve GPS radio sources at 5 GHz

Abstract: Aims. Gigahertz peaked spectrum (GPS) radio sources are compact extragalactic radio sources, assumed to be young radio-loud active galactic nuclei and ideal objects for studying the early evolution of extragalactic radio sources. The Very Long Baseline Interferometry (VLBI) observation with high resolution is vital for studying the structure of these compact sources. Methods. We defined a sub-sample of twelve GPS sources which have not been observed with the VLBI before, from the Parkes half-Jansky sample, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The light curve shows a gentle positive slope of variability (M = 4.3%) with significance ∇S = 6.3 over the entire time-scale of observations (see Figure 5). Cui et al (2010) carried out 5 GHz monitoring over a period of several years and found no significant variability. This object has been monitored for 15 years at 408 MHz (Bondi et al 1996) with a modulation index of 3.2%.…”
Section: Gleam J032320+053413 (Pks B0320+055mentioning
confidence: 99%
“…The light curve shows a gentle positive slope of variability (M = 4.3%) with significance ∇S = 6.3 over the entire time-scale of observations (see Figure 5). Cui et al (2010) carried out 5 GHz monitoring over a period of several years and found no significant variability. This object has been monitored for 15 years at 408 MHz (Bondi et al 1996) with a modulation index of 3.2%.…”
Section: Gleam J032320+053413 (Pks B0320+055mentioning
confidence: 99%
“…In addition, the VLBI flux density at 15 GHz decreases significantly, which again contradicts a classical CSO, whose flux is quite stable on the time scale of years (e.g. Cui et al 2010;An & Baan 2012;Tremblay et al 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Merloni et al 2003;Liodakis et al 2017). Figure 6 plots the projected linear size of jets versus the BH mass for the six VLBI-detected dwarf AGNs, some young radio sources (O'Dea 1998;Snellen et al 2003;de Vries et al 2009;Kunert-Bajraszewska et al 2010;Cui et al 2010;An & Baan 2012;Orienti & Dallacasa 2012), and Fanaroff-Riley (FR) I and II radio galaxies (Black et al 1992;Nilsson et al 1993;de Koff et al 1996;Martel et al 1999;Harvanek & Stocke 2002;Chandola et al 2013). The additional data for the more massive BHs at 𝑧 < 4 were firstly collected by Liao & Gu (2020).…”
Section: Sourcementioning
confidence: 99%